Pace and Space in Naturalist and Realist Novel: The Case of Germinal (ENTHYMEMA, 2025)
This study examines the temporal and spatial qualities associated with realist and naturalist novels in general and with Émile Zola’s Germinal in particular. It is based on the assumption that the spatial-temporal qualities of both realist and naturalist genres are fundamentally determined by the pragmatic aspects of literary realism and naturalism, as outlined by early realist thinkers and writers such as Guy de Maupassant, George Eliot, Gustav Flaubert, the de Goncourt brothers, Henry James, Émile Zola, and others. The study aims to provide a deeper understanding of spatial-temporal qualities and the ways in which they contribute to the genre’s distinctive style and impact. By examining these qualities in detail, the paper sheds light on the vital role that naturalist novels play in reflecting and shaping our understanding of the world. The study uses Émile Zola’s Germinal (1885) as a primary referential framework to exemplify the theoretical findings.
Keywords: Realism; Naturalism; Germinal; Novel; Émile Zola